Metodologia de projeto em design: ensino em uma realidade complexa que busca a sustentabilidade - Pons, Ivo Eduardo Roman (2011)
This research deals with the teaching of product design methodology in Design, Industrial Design and similar courses which offer a bachelor s degree in product design within Graduate Institutes. The methodologies applied to the subjects concerned will be discussed in this paper, as well as their effectiveness in preparing alumni to tackle complex problems related to both sustainability and the sustainable development of our society. Founded on extensive field research, which led to the main publications introduced by the Design courses all over Brazil, the research also enquired Professors who teach both product design and product design methodology at Graduate Institutes, as well as their alumni. The main publications employed were analyzed, and their fundamental characteristics were highlighted. A timeline regarding sustainability and a map of complexity aided in comparing and criticizing the product design methodological structures currently employed, having as a final outcome a critical discussion and an indication of necessary changes in the teaching of methodology in Design courses in Brazil